PENGARUH TERAPI LATIHAN DAN PEMASANGAN BANDAGE PADA CONGENITAL TALIPES EQUINO VARUS BILATERAL DI YPAC SEMARANG : LAPORAN KASUS - Didik Purnomo; Irawan Wibisono; Rahma Nurwidianti (Universitas Widya Husada Semarang, 2019)
Background : Congenital Talipes Equino Varus (CTEV) or commonly called Clubfoot is a general term used to describe a general deformity which is foot changes from its normal position. Problems that occur in the Congenital Talipes Equino Varus Bilateral case are the limited range of motion on both ankles, the presence of contractures in the posterior tibialis muscle. Physiotherapy role by providing modalities such as bandage usage, stretching, wall bars exercise, parallel bars exrcise and easy standing exercise.Case Presentation : Patients in this case were 9-year-old women using interventions in the form of bandage usage, wall bars exercise, parallel bars exrcise and easy standing exercise for 6 sessions.Method : This case report assesses the patient's joint motion range by measuring differences between pre-test and post-test.Results: Patients do not improved in the ankle range of motion.Conclusion : In this case, it was shown that exercise therapy given and bandage usage on 9-year-old patients with CTEV conditions could not change the patient's ankle range of motions.